Corporate Distress in East Asia : The Effect of Currency and Interest Rate Shocks - Claessens, Stijn; Djankov, Simeon; Ferri, Giovanni (World Bank, Washington, DC, 2012)
A study of the five countries most affected by the East Asian financial crisis - Indonesia, the Republic of Korea, Malaysia, the Philippines, and Thailand -- shows that more than 60 percent of firms are illiquid and 30 percent are technically insolvent. Among solvent firms, about half are at risk of insolvency unless their liquidity constraints are relieved. Worst affected is Indonesia, with 77 percent of firms illiquid and 65 percent insolvent, followed by Korea and Thailand. Extrapolations using these findings suggest that non-performing loans in the five countries could amount to 7 to 30 percent of Gross Domestic Product (GDP) and non-performing assets to more than a third of their combined GDP.